Design Development of Sprinkler Irrigation System To Protect The Failed Harvest of Citrus “Keprok 55” In Dry Season at Selorejo, Dau, Malang - Bambang Suharto; Liliya Dewi Susanawati (Research Journal of Life Science, 2016)
This study is a part of ongoing research to mainstay citrus productivity in Malang region. Therefore, the specific aim of this study is developing the design of sprinkle irrigation in field. Selorejois central location of citrus production called “KEPROK 55” in Dau-Malang. The cultivation requires maintenance of soil and plants, in addition the lower of citrus production especially in dry season thus indispensable an effort to increase the production. Application of technology using sprinkle irrigation is expected to create the increasing of Citrus production. Result on research study show that the coefficient of uniformity tends to have same value on all the treatment that is above 98%, where the average value of the coefficient of uniformity was 98.8%. The highest value of the coefficient of uniformity achieved at combination of treatment P1T1 (pressure of 1 bar with a riser pipe 50 cm height) that is equal to 99.78%. While the coefficient of uniformity was lowest at the combination of treatment P2T3 (pressure of 1.5 bar with a riser pipe 150 cm height) by 96.6%. The pressure effected to the coefficient of uniformity indicates that the greater pressure exerted, then the coefficient of uniformity will be higher. It indicated at the treatment of pressure P1, P2, and P3 (1 bar, 1.5 bar and 2 bar) that have the average coefficient of uniformity of 98.53%, 98.27%, and 99.64%.